Mindfulness para pacientes em cuidados paliativos. Revisão sistemática de literatura - Latorraca, Carolina de Oliveira Cruz [UNIFESP] (2017)
Objective: To assess effectiveness and safety of mindfulness for patients receiving palliative care. Methods: Systematic review of randomized controlled trials. Search strategy was run in several databases, namely CENTRAL, MEDLINE, Embase, LILACS, PEDro, CINAHL, PsycINFO, and Open Grey. Databases for register of clinical trials (ClinicalTrials.gov e WHO-ICTRP) were also searched. No restriction of language or date of publication was imposed. Clinical trials focusing on the effectiveness of mindfulness for adults receiving palliative care were included. Comparisons included any scheme of mindfulness versus placebo/sham, no treatment, psychotherapy, or equivalent types of interventions. Primary outcomes included quality of life, symptom management, functional status and adverse events. Methodological quality of included studies was appraised by the use of Cochrane Risk of Bias Table. Screening, data extraction and critical appraisal were performed independently by two reviewers. Quality of evidence was appraised by Grading of Recommendations Assessment, Development and Evaluation (GRADE). Mean differences (MD) with confidence intervals of 95% (CI 95%) were calculated as the estimate of effect size. Results: Four studies (234 participants) comparing different schemes and techniques of mindfulness were included. All of these studies were considered high risk of bias for at least one out of the six criteria in Risk of Bias Table. Comparisons included: Comparison 1: mindfulness (six sessions of 45 minutes each, one session per week) versus no treatment (one study); Comparison 2: mindfulness (single session of 90 minutes) versus no treatment (one study); Comparison 3: mindfulness (single session of five minutes) versus control (five standard semistructured questions in five minutes) (one study); Comparison 4: mindfulness (one session per week for eight weeks) versus support group for chronic pulmonary obstructive disease patients as the control (one study). Only three studies evaluate at least one of the primary outcomes elected for this review. As assessed by GRADE, the quality of evidence for each outcome was as follows. Comparison 1, outcome ‘severity of symptoms’, quality of evidence very low, outcome ‘quality of life – physical aspects’, quality of evidence very low, outcome ‘quality of life – mental aspects’, quality of evidence very low; Comparison 4, outcome ‘quality of life – activity subscore’, quality of evidence very low, outcome ‘quality of life – symptoms subscore’, quality of evidence very low, outcome ‘quality of life – impact subscore’, quality of evidence very low, outcome ‘quality of life – physical aspects’, quality of evidence low, outcome ‘quality of life – mental aspects’, quality of evidence very low, outcome ‘symptom experience’, quality of evidence low. Considering all outcomes reported in the aforementioned comparisons, mindfulness seems to be beneficial only for the outcome 'improvement in levels of stress perceived by patients’ in two time points, just after the intervention (MD -1,80; CI 95% -1,99 to -0,17; 60 participants, p = 0,02) and 10 minutes after the intervention (MD -1,05, CI 95% -1,94 to -0,16; p = 0,02). Conversely, mindfulness was associated with worsening of 'physical aspects of quality of life', when compared to no intervention (MD -4,30, CI 95% -7,99 to -0,61; p = 0,02; quality of evidence low). Conclusions: Evidences on the effects of mindfulness for patients receiving palliative care are of very low quality, preventing treatment effects to be properly estimated and practical recommendations to be made. High-quality randomized controlled trials are needed to determine the effects of mindfulness for patients receiving palliative care, and to enable the establishment of practical recommendations.